Breastfeeding behind bars: Experiences of incarcerated mothers in the Spanish penitentiary system - Pilar Jubany-Roig; Ester Massó Guijarro (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
This research aims to analyze the breastfeeding experiences of incarcerated mothers in the prisons of the Spanish penitentiary system. Additionally, it explores whether these mothers have perceived practices related to obstetric violence during pregnancy, childbirth, and the postpartum period. An exploratory-descriptive study was conducted using a qualitative approach and a critical ethnographic method. Fieldwork, including participant observation and semi-structured interviews, was carried out between December 2021 and April 2022. The study involved 30 adult women from Africa, Europe, Eastern Europe, and Latin America, all serving sentences with their infants in Mother Units located in the Spanish cities of Alicante, Barcelona, Madrid, and Seville. The main findings highlight the need for penitentiary policies with a gender and feminist perspective. These policies should aim to eliminate severe inequalities and discriminations faced by incarcerated women while protecting the basic rights of both mothers and infants.